Quantum chemical investigation of lanthanum doping effects in tetragonal and rhombohedral PZT materials - Stashans, A. (2008)
tructural and electronic properties of lead-zirconate-titanate (PZT) materials doped with a lanthanum (La) impurity are studied using a quantum-chemical approach based on the Hartree-Fock theory. Performed geometry optimization in the defective crystals shows that the atomic movements are predominantly outward with respect to the impurity position. It is found that the La impurity enhances a covalent character in the chemical bonding between the Ti and O atoms, as well as the Zr and O atoms situated in the neighborhood of the defect despite the fact that the La-O interaction remains purely ionic. The occurrence of local energy levels within the band gap of the material is analyzed in light of the available experimental data on La concentration influence upon dielectric and piezoelectric properties in these crystals. © 2009 Wiley Periodicals, Inc.